Transformation of Property Register in the Digital Age: Evidence from Ukraine - Alieksieiev, Ihor; Pozniakova, Olena; Dobosh, Nazar; Syniutka, Nataliya (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The article is devoted to the problem of the need to transform the property register on the example of Ukraine. Existing registers do not accumulate all the necessary information on property, while the effects of unauthorized concentration and hidden monopolies are present in many countries around the world. Concentration of ownership poses a threat not only due to the deterioration of the economic situation, business activity of many market participants, but also due to the threat to the economic security of the country. Antitrust law does not always effectively regulate antitrust actions and focuses more on changes in ownership (ownership shares, asset values). However, most cases of concentration and hidden monopolies occur in terms of use and disposal, in particular through the institution of trust management. It is proposed to create a single property register, which will have a completely new approach to grouping information and its use. Information on property of both individuals and legal entities is proposed to be provided using matrices based on the triad of property rights: ownership, use and disposal. This information should be accumulated from all existing registers. The elements that will form the matrices will be considered both from the standpoint of the owner and from the standpoint of the beneficiary. The data of the unified property register will be useful both for antitrust regulation and in assessing the feasibility of property transformations by public authorities for decision-making on privatization. The authors suggest that consolidating all information into a single register would not only prevent veiled forms of concentration and provide more effective regulation of property transformations, but become the basis for the formation of the ownership history of each entity such as credit history. We believe that digitalization processes can significantly help to improve the register and provide new opportunities for collecting and creating a database.